Child Rights in India, 1st ed. - Chopra, Geeta (Springer, 2022)
The book is a comprehensive compendium on child rights in India from a child development perspective. It discusses the challenges that Indian children face for survival, development and education, especially if they are marginalized through disability, lack of care, and poverty. The major issues expounded by the author in relation to rights are infant and child survival, early child development, street and working children, children in conflict with law, children with disabilities, child trafficking and child sexual abuse. The author goes further to delve into the causes, among which are high population, poverty, migration, illiteracy, poor legislation and deep-rooted social norms and behaviour. The book presents the existing policy and legal framework in India for each of these issues. The broad purpose of the book is to comprehensively discuss the roadblocks that the marginalized child in India faces, to understand the causes of these roadblocks and to evaluate government and civil society action for children in India.